Identifikasi Waste Pada Proses Produksi Key Set Clarinet Dengan Pendekatan Lean Manufacturing - Dana Marsetiya Utama; Shanty Kusuma Dewi; Veronika Indah Mawarti (Jurnal Ilmiah Teknik Industri, 2016)
This study discusses lean manufacturing concept to identify waste in Key Set Clarinet production process at Yamaha Musical Products Indonesia, Ltd. The lean manufacturing concept is done intially by big picture mapping, waste assessment model (WAM), value stream mapping (VSM) and cause and effect diagram respectively. The results show that the dominant waste is defect (26.04%), motion (19.34%), inventory (19.22%), and waiting (13.91%).